Women`s football in Southern Africa: An exploratory study of the challenges facing international players - Bahdur, K. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction Governments and sports federations are prioritizing women`s sport. The Federation Internationale de Football Association (FIFA) have made commitments and allocated resources to member associations (MA) to help them provide better support, better resources, and create an environment to enable more opportunities for female players. More MA are developing strategies for women`s football. However, despite increased opportunities to compete, challenges still arise in creating the best environment for players to fulfil their potential. Methods This informal qualitative explorative study delved deeper into challenges facing Southern African footballers. Discussions which centered around individual player`s development and the challenges facing them, were held with 70 English-speaking players from 5 senior women`s national teams. Narrative analysis was used to analyse the data. During the discussions, information was clarified, and time was taken to ensure that the interpretation was correct. Consistent themes in the discussions were identified. Results Two main general themes were identified. These related to lack of resources and lack of support. Lack of resources extended to facilities, expertise, and financial resources. Lack of support centered around family, friends and extended to the broader community. A key point that was highlighted was that evidence-based solutions must explore both the homogenous and the heterogenous nature within an African women`s context. Discussion The findings revealed that while progress in the women`s game must be acknowledged, there remain challenges facing players within Southern Africa. The importance of training as well as the resources required for training and the holistic improvement of players are often not a focal area away from international tournaments. Players highlighted the difficulty in improving without enough exposure to high training stimuli. They also mentioned being required to work individually on training, which is challenging in a team sport often leads to often feeling isolated. Even players who seek new and better methods of training, recovery and conditioning tools, are often limited by socioeconomic constraints, or in the case of nutrition, solutions that are Eurocentric and not feasible in the African context. The socioeconomic challenges facing the continent extend to football resources. These challenges are exacerbated due to the remaining gender stereotypes, cultural norms and firm opposition regarding women`s involvement in football. The lack of support can sometimes extend to active critique and undermining of a player`s football dreams. Balancing the expectations and venturing towards what community, family and friends see as an undesirable pathway, with one`s own vision for their life adds feelings of conflict, guilt and greater conflict for players. More applied research is required to produce evidence-based solutions that are feasible within an African context.